Quantitative Detection of Adulterated Apple Components in European Sweet Cherries by Droplet Digital PCR - Jia CHEN; Li QIN; Hao LIU; Bo YANG; Kaijiang ZHANG; Dongmei ZHAO; Jinying GUO; Yuanyuan ZHANG (Shipin gongye ke-ji, 2022)
Objective: To establish a method for quantitative detection of adulterated apple components in cherry based on droplet digital PCR (ddPCR). Methods: By screening the component specific primer probes of cherry and apple, the quantitative detection method of ddPCR was established. The fitting curve between quality and DNA content and the fitting curve between DNA content and copy number were constructed. Taking DNA content as the intermediate value, the calculation formulas of quality and amplified copy number were obtained. The linear fitting curves R2 were all above 0.99, and the corresponding adulteration model was established to verify the accuracy of the method. Results: The formula for calculating the mass and amplified DNA copy number of cherry and apple: Mcherry=0.0833C−3.8420, Mapple=0.4084C−1.5747. In the adulteration model of cherries and apples, the maximum relative error was −19.17%, which met the statistical requirements. Conclusion: The establishment of a rapid detection method for European sweet cherry products provides a powerful means to combat the adulteration of European sweet cherries, protects the rights and interests of consumers, and is of great significance for promoting the healthy development of the small berry and its product industry.